Mekanika Turbin Dan Fungsinya Untuk Merubah Energi Turbin Dan Peralatan Pembantu - Askan (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2013)
Irrigate admission rifting of disuplay by pump by continue tying save at LP heater to deaerasi. Irrigate admission filling flow out from LP heater after can mach saturated temperature according to specification of in area violate. Stream direction of admission filling is to reverse go to stream direction condense to yield to increase of efficiency. Outside tube, vapour discharged to become admission filling water and condensation become kondencate dropp to go down into shell. Kondencate will be channelled to become as according to stream method mount per storey; level from which is higher level pressure to having water to lower lastly [of water of kondencate of LP heater will be dissociated to liquefier